ACTUAL PROBLEMS OF ATHLETES’ HEALTHY NUTRITION - Buranova Gulnoza Boymuratovna, Xosilova Ziyofat Begmuratovna (American Journal of Biodiversity, 2024)
The article presents the results of a study of the actual nutrition of wrestlers and their analysis. At the same time, the actual nutrition of the subjects was studied in appropriate ways, and the results obtained were compared with the norm and analyzed. Based on the collected data, the corresponding conclusion was made. The necessary recommendations on the organization of a healthy diet for athletes are also given.